(untitled) (Research, Society and Development, 2021)
Objective: Describe the main clinical findings of post-cholecystectomy syndrome and irritable bowel syndrome. Case Report: Post-cholecystectomy syndrome (SPC) is the term used to describe the persistence of biliary colic or abdominal pain in the upper right quadrant with a variety of gastrointestinal symptoms, similar to the characteristics experienced by an individual before cholecystectomy. These symptoms include intolerance to fatty foods, nausea, vomiting, heartburn, flatulence, indigestion, diarrhea, jaundice and intermittent episodes of abdominal pain. SPC can present itself in the postoperative period, as well as it can manifest months to years after the surgery. Irritable bowel syndrome (IBS) is a chronic functional disorder of the gastrointestinal tract characterized by recurrent abdominal pain and altered bowel habits, at least one day a week for three months with two or more of the following items: defecation, associated with a change in frequency of stools or associated with a change in the shape (appearance) of the stools, in the absence of an organic pathology. It is also known that the association of the two syndromes is a rare event, and biliary, extra-biliary and psychogenic causes should be investigated. Final Considerations: The purpose of this case report is to add information about the two syndromes.